Meningkatkan Hasil Belajar Menggunakan Model Problem Based Learning Pada Kelas V SDN 1 Batu Meranti - Tri Rohmah Putri Pratiwi; Sunarno (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this study is the low student learning outcomes. To overcome these problems, researchers used the Problem Based Learning model. The purpose of this study was to describe teacher activities, analyze student activities and learning outcomes. The approach used in this study is qualitative research with the type of Classroom Action Research (CAR). The research subjects were fifth grade students at SDN 1 Batu Meranti, Tanah Bumbu Regency, for the 2022/2023 school year, with a total of 22 students. The type of research data is qualitative and quantitative data. Data analysis uses descriptive, tables and graphs. The results of this study indicate that there was an increase in teacher activity in the first cycle to get a score of 19 which was presented to 79.2%, in the second cycle it increased to 100% to get a score of 24 with the "Very Good" criterion. This increase in teacher activity affects student activity where in cycle I with a percentage of 63.6% it increases classically in cycle II to 90.9% or student activity meets the established criteria, namely ≥80% of the total number of students. It can be concluded that teacher activity, student activity and student learning outcomes have increased significantly by using the Problem Based Learning (PBL) model so that teachers and other researchers can use it as an alternative to improve learning outcomes.